Removal of carbamazepine, diclofenac and trimethoprim by solar driven advanced oxidation processes in a compound triangular collector based reactor: A comparison between homogeneous and heterogeneous processes. (January 2020) - Kowalska, K.; Maniakova, G.; Carotenuto, M.; Sacco, O.; Vaiano, V.; Lofrano, G.; Rizzo, L.
Abstract: Contaminants of emerging concern (including pharmaceuticals) are not effectively removed by municipal wastewater treatment plants (WWTPs), so particular concern is related to agricultural wastewater reuse due to their possible uptake in crops irrigated with WWTPs effluents. Advanced oxidation processes (AOPs) and solar AOPs have been demonstrated to effectively remove pharmaceuticals from different aqueous matrices. In this study, an heterogeneous photocatalytic process using powdered nitrogen-doped TiO2 immobilized on polystyrene spheres (sunlight/N–TiO2 ) was compared to the benchmark homogenous AOP sunlight/H2 O2 in a compound triangular collector reactor, to evaluate the degradation of three pharmaceuticals (carbamazepine (CBZ), diclofenac (DCF), trimethoprim (TMP)) in water. The degradation of the contaminants by sunlight and sunlight-AOPs well fit the pseudo-first order kinetic model (but for TMP under sunlight). High removal efficiency by solar photolysis was observed for DCF (up to 100%, half-life sunlight cumulative energy QS, 1/2 = 2 kJ L −1, half-life time t1/2 = 32 min), while CBZ (32%, QS, 1/2 = 28 kJ L −1, t1/2 = 385 min) and TMP (5% removal after 300 min) removal was poor. The degradation rate of CBZ, TMP and DCF was found to be slower during sunlight/H2 O2 (QS, 1/2 = 5 kJ L −1, t1/2 = 77 min; QS, 1/2 = 20 kJ L −1, t1/2 = 128 min; QS, 1/2 = 4 kJ L −1, t1/2 = 27 min, respectively) compared to sunlight/N–TiO2 (QS, 1/2 = 4 kJ L −1, t1/2 = 55 min; QS, 1/2 = 3 kJ L −1, t1/2 = 42 min; QS, 1/2 = 2 kJ L −1, t1/2 = 25 min, respectively). These results are promising in terms of solar technology upscale because the faster degradation kinetics observed for sunlight/N–TiO2 process would result in smaller treatment volume, thus possibly perspective compensating the cost of the photocatalyst. Graphical abstract: Image 1 Highlights: Comparison between homogeneous and heterogeneous solar driven AOPs. The degradation of the contaminants well fit pseudo-first order kinetic model. Diclofenac effectively degraded even by solar photolysis. Faster degradation of pharmaceuticals by sunlight/N–TiO2 compared to sunlight/H2 O2 . Sunlight/N–TiO2 process would result in a smaller treatment volume than sunlight/H2 O2 .